IMPROVING STUDENTS’ READING SKILLS USING NARATIVE TEXT OF TENTH GRADE AT SMA NEGERI 2 TONDANO - Jelmiati Ambana; Paula Rombepajung; Fridolin Kukus (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study was to determine whether employing narrative texts could effectively improve the reading abilities of students in SMA Negeri 2 Tondano's tenth grade. This study employed a pre-experimental design with pre- and post-tests conducted on two groups, and a make a match treatment. As a result, post-test scores were better than pre-test scores. The post-test result was better than the pre-test since the mean score for the pre-test was 4.85 and the mean score for the post-test was 7.25. It may be said that SMA Negeri 2 Tondano students have strong reading abilities in the tenth grade. Even with a little treatment it can make them active in responding to a number of things that need to be improved in narrative text skills. So, the tenth grade pupils at SMA Negeri 2 Tondano were able to read more fluently thanks to narrative text, even just using a small treatment in the middle of learning.